Protective action of lemongrass essential oil on mucilage from chia (Salvia hispanica) seeds. (August 2020) - Cuomo, Francesca; Iacovino, Silvio; Messia, Maria Cristina; Sacco, Pasquale; Lopez, Francesco
Abstract: Mucilage extracted from chia seeds ( Salvia hispanica ) is reckoning an increasing interest for its mechanical and nutritional properties. Freeze-dried mucilage dispersed in solvent undergoes degradation, through autoxidation phenomena, that results in the loss of the initial rheological characteristics. In order to limit the extent of depolymerization, an essential oil (lemongrass essential oil, LEO) is here emulsified with chia mucilage (CM) suspensions, and the rheological behavior of samples containing LEO or not compared. Flow curves of CM suspensions and of CM emulsions dispersing LEO (O/W-CM) demonstrated that both the systems can be classified as plastic fluids, and that during storage a general decrease of the viscosity of CM suspensions is detected, while the viscosity of the O/W-CM systems remaining constant. The differences between the two systems were also confirmed by oscillatory tests and through measurements of intrinsic viscosity. By means of an accelerated oxidative test, it was unveiled that the short-term stability of CM suspensions is attributable to the reaction of oxidation, and that the presence of LEO, due to its anti-oxidative properties, allowed for preventing degradation phenomena on the chia mucilage. We conclude that the colloidal stability of chia-based mixtures can definitely be improved following to LEO treatment - hence forming an emulsion - thereby preventing short-term polymer degradation. Graphical abstract: Image 1 Highlights: Essential oil is emulsified in chia mucilage suspensions. The rheological behavior of emulsion and suspensions were different during storage. Mucilage suspensions undergo degradation during storage. Essential oil prevents the degradation phenomena on the chia mucilage.